About the choice of tension for canvas paintings - Antonio Iaccarino Idelson (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The choice of the value of tension for a canvas painting is crucial for its future life, but tradition has handed us methods based on intuition that do not allow us comparing the results of different choices. Since the 1950es it is possible to measure the force used for stretching a painting, but this is very rarely done. This paper describes the evolution of the approach to the problem and points out the results of recent research and changes in attitude.